Implementasi Algoritma Collision Detection pada Game Simulator Driving Car - Lui Haekal Fasha; Fauziah Fauziah; M. Gufroni (Universitas Indraprasta PGRI Jakarta, 2018)
Currently, there are so many game engines that can be used to design and create games. One of them is Unity 3D. It is now a game engine widely used not only by a person to design or create games but also by some developers to produce games. Collision Detector Algorithm is a method of detecting reaction produced by a collision between two or more objects. The method is primarily used in the animation and game production. The researcher uses this method to design a driving simulation game, in which a player hitting obstacles that have been stacked on a track will experience reaction from one of the specified obstacles. From the results of this study, it can be concluded that the Fps obtained in this game reaches its best point at around 60 Frame Per Second and its worst point at around 24.6 Frame Per Second.